RISIKO DAN RETURN INVESTASI SAHAM DALAM MENENTUKAN KEPUTUSAN INVESTASI - Jufri Sani Akbar (LPPM STIE PERTIBA Pangkalpinang, 2021)
Investment risk occurs due to the difference between the expected rate of return with the actual rate of return, conditions of uncertainty will cause unwanted risk. Investors will feel safe if macroeconomic conditions are good, inflation is under control, exchange rates strengthen and interest rates are low. In investing, investors expect a return, either in the form of dividends or capital gains. The expected return on Indosat shares as the case study is 4.32% for a period of six months from June to November 2021, while the magnitude of the risk for the shares is 7.52%. The second case study is Telkom's stock, where the expected return is 2.87% and the stock risk is 5.39%. In addition to analyzing the respective stocks, stocks are also analyzed in the form of a portfolio with a case study combining the two stocks. From the results of portfolio analysis, it is obtained that the expected return is 3.96% with the allocation of funds of 75% and 25%, the expected return is the highest from the alternative allocation of investment funds, while the portfolio risk is 0.16%. Investment decisions on the basis of risk and return are influenced by the attitude of investors in facing risk. If investors want to get a large return, then the choice falls on the ISAT stock code, if investors want low risk, then the choice falls on the TLKM stock code, and if investors want both stocks, then the investment decision is taken in the form of a portfolio with a return of 3.96% and a risk of 0.16%. Keywords: Risk, Return and Investment Decision